Outdoor tourism in the North of Portugal from the perspective of tourist entertainment companies (TEC) - Martins, Oliva M.D. (2021)
Based on the perception of those responsible for Tourist Entertainment Companies (TEC), the objective of the research is to contribute to the characterization of Outdoor Tourism (OT). Exploratory qualitative research was carried out through 38 in-depth individual interviews. The territory geography, the experiences, and the internal market were considered relevant aspects. In addition, seasonality and climate were identified as significant factors in defining the offer, which can favour the preservation of the environment. Moreover, the risk of the activities was considered low. The interviewees suggested integrating everyone involved in a network to explore the region's potential, as well as to support activities and promote the region. The radical experience, adventure, and getting out of the routine were identified as motivations for the search, as well as contact with nature and the landscape. The research is limited to the North Region of Portugal, and it brings together the most different needs, desires, and expectations for tourism demand. Strengthening OT can favour employability and, consequently, economic and social balance while promotion of the activity can be explored through the customers' previous experience. The evaluations, testimonials, and word of mouth (WOM) being added value that can be optimized through social networks and digital marketing.